Multiscale and Correlative Analytical Electron Microscopy of Extraterrestrial Minerals - Albu, Mihaela; Fitzek, Harald; Moser, David; Kothleitner, Gerald; Hofer, Ferdinand (Frontiers in Astronomy and Space Sciences, 2020)
This paper presents a unique correlative microscopic method for the structural characterization of extraterrestrial minerals. A fragment from the pallasite Seymchan meteorite that consists of olivine grains mixed into a metallic iron matrix with variable nickel content was studied from mm-down to nm-size by using the Raman Imaging and Scanning Electron Microscopy and analytical scanning transmission electron microscopy. Hyperspectral fast acquisition for energy-dispersive X-ray spectroscopy mapping of a couple of mm2 large area correlated with additional hyperspectral Raman analysis of smaller regions in the same area on one hand, and hyperspectral analytic STEM investigations at the atomic resolution, on the other hand, provided valuable information about the chemical composition, bonding, and crystallography. The analysis revealed particles of troilite, schreibersite, and forsterite but also regions of mixed iron oxides, carbonates, and amorphous carbon as well as plessite regions with nanometre-sized taenite needles dispersed in the kamacite matrix.